1997
DOI: 10.1016/s0014-5793(97)00813-2
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the mouse 5‐HT7 receptor: importance of the third intracellular loop for receptor–G‐protein interaction

Abstract: The mouse serotonin (5-HT) receptor subtype, 5-HT7, belongs to the family of seven transmembrane G-proteincoupled receptors. To identify the structural basis for the coupling of 5-HT 7 receptor to Gas we constructed a number of receptor mutants in which amino acid residues were either substituted or deleted from the second and third intracellular loops. Wild-type and mutant 5-HT 7 receptors were expressed in insect cells using the baculovirus vectors. Two mutant receptor species, 5-HT 7 (E325G) and 5-HT 7 (K32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The insertion of GFP into the third-intracellular loop had no apparent effect on coupling, as SER-7B and SER-7BI3GFP had nearly identical EC 50 s for the 5-HTdependent stimulation of cAMP levels, when the receptors were transiently expressed in COS-7 cells (30 6 3 nm vs. 47 6 5 nm, respectively, Figure 2). In addition, the expression of a modified SER-7B (SER-7B E314A/ K316A I3GFP) designed to couple less effectively to Gproteins by mutation of key amino acids in the thirdintracellular loop of the receptor ( Figure 1B; Obosi et al 1997), also failed to generate robust transgenic lines under the control of the same promoter . As predicted, when SER-7B E314A/K316A I3GFP was expressed in COS-7 cells, the 5-HT stimulation of cAMP levels was dramatically reduced compared to SER-7B, with an EC 50 of 1.8 6 0.5 mM and a maximal activation of less than half that of SER-7B, suggesting that SER-7B E314A/K316 I3GFP was functional, but attenuated (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The insertion of GFP into the third-intracellular loop had no apparent effect on coupling, as SER-7B and SER-7BI3GFP had nearly identical EC 50 s for the 5-HTdependent stimulation of cAMP levels, when the receptors were transiently expressed in COS-7 cells (30 6 3 nm vs. 47 6 5 nm, respectively, Figure 2). In addition, the expression of a modified SER-7B (SER-7B E314A/ K316A I3GFP) designed to couple less effectively to Gproteins by mutation of key amino acids in the thirdintracellular loop of the receptor ( Figure 1B; Obosi et al 1997), also failed to generate robust transgenic lines under the control of the same promoter . As predicted, when SER-7B E314A/K316A I3GFP was expressed in COS-7 cells, the 5-HT stimulation of cAMP levels was dramatically reduced compared to SER-7B, with an EC 50 of 1.8 6 0.5 mM and a maximal activation of less than half that of SER-7B, suggesting that SER-7B E314A/K316 I3GFP was functional, but attenuated (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…2002), cytosolic cationic clusters can serve as docking sites for regulatory proteins (Obosi et al . 1997; Wang, , ), and can anchor proteins to negatively charged head groups of phospholipids in the inner leaflet of lipid bilayer (van Klompenburg et al . 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of the basic residues in a motif present at the carboxyl-terminal end of the third intracellular loop of many class A GPCRs, having the sequence BBxxB or BxxBB, has been shown to decrease or eliminate agonist-induced G protein activity (24,36,40,42,47,68). Some studies have demonstrated that exchanging the third intracellular loop regions of distinct GPCRs can result in a shift in the specificity of the interacting G protein (71,72).…”
Section: Discussionmentioning
confidence: 99%